Fold catastrophe analysis of constitutive model of pick cutting coal with rock - Chenxu Luo (Elsevier, 2022)
Considering the failure mechanism of pick cutting coal & rock, combined with the cutting load test, the single pick load of cutting coal & rock is obtained and analyzed,​ based on the load of single coal & rock caving load change process in time domain analysis, establish the fold catastrophe theory model of cutting load, qualitative analysis, the change rule of cutting load and provide theoretical basis for the further study of cutting load. The single fracture load equation in cutting was obtained by numerical fitting, the load characteristics and change rule were analyzed by catastrophe theory, the coal–rock cutting system dynamics model was established. The mutation characteristics of coal and rock breaking process for pick pressing into the coal and rock until spallation are revealed, and the mutation mechanical model taking the load as disturbance factor is established. The stiffness of the cutting system plays an important role in cutting. The dynamic crushing load change process of coal–rock cutting mechanical system can be well described by catastrophe theory.